Citra Sosial Perempuan Dalam Keluarga: Kajian Kritik Sastra Feminis dalam Cerpen Kutunggu Kau di Jakarta Karya K.Usman - Jumianti Diana (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This article is about the social image of women in the family found in the short story Ku Tunggu Kau Di Jakarta by K. Usman. It is one of the titles of short stories found in the collection of short stories called Menari Di Atas Air. The storyboard was analysed using feminist literary criticisms. Studies have shown that a female figure named Mawarni was treated as a child and as a wife in the family. As a child, Mawarni was hurt from childhood until marriage he was an obedient child, he always did what his parents wanted him to do. However, after marrying Jumeno, his father considered him a rebellious child. He was actually a child who tried to muster up the courage to express his wishes. She wanted to join her husband who lived in Jakarta. After saying good-bye three times and still not letting her parents leave, she made her own decision. She chose to go to Jakarta after her husband. As a wife, she also wanted to experience the freedom of life far away from her parents. He left the house that his parents had given him.